Estudo exploratório sobre dificuldades de estudantes do curso de ciências biológicas da Universidade Federal do Oeste do Pará na compreensão do conceito de função - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2020)
This work consists of a study conducted with students from the Universidade Federal do Oeste do Pará, whose objective was to map difficulties faced in understanding the concept of function. Records from two groups of students were analyzed, the first being students from a biology undergraduate class and the second is comprised of bachelor students in biology and health engineering. The methodology used was based on content analysis, a method also used in qualitative data analysis, and was based on the theory of conceptual fields, a cognitive theory of the concept. The main obstacles encountered were associated with the absence of mathematical knowledge, explanation of elements and mathematical properties and their relations, reduction of the resolution of a situation to an algorithm, and difficulty in establishing a relationship between different forms of representation of a situation involving the concept.
Keywords: Campos Conceituais; Função; Dificuldades; CNPQ:: CIÊNCIAS EXATAS E DA TERRA